The Impact of Diabetes Education on Continuous Glucose Monitoring in SUS-Dependent Patients in a Northeastern Brazilian City - Lysandro Pinto Borges; Pamela Chaves de Jesus; Jessiane Bispo de Souza; Deise Maria Rego Rodrigues Silva; Pedro Henrique Macedo Moura; Ronaldy Santana Santos; Marina dos Santos Barreto; Adriana Gibara Guimarães; Lucas Alves da Mota Santana; Dennyson Leandro Mathias da Fonseca; Ikaro Daniel de Carvalho Barreto; Breno de Mello Silva; et al. (Life, 2024)
Background: Diabetes Mellitus (DM) is an important chronic disease that occurs worldwide. Aims: This study aims to investigate how the use of the FreeStyle® Libre system in Unified Health System (SUS) patients impacts diabetes parameters in patients who receive education on proper insulin administration and the use of the continuous monitoring device, as well as how this affects patients without any concomitant multidisciplinary support in Sergipe, Brazil. Methods: We conducted a prospective randomized study in a diabetes clinic in Sergipe, Brazil, using the flash method FreeStyle® Libre (Abbott). The participants were divided into two groups: one receiving diabetes education on CGM (continuous glucose monitoring), while the other did not. Before the intervention, the patient’s treatment motivation and quality of life were assessed using a questionnaire, and baseline levels of glycated hemoglobin were measured using high-performance liquid chromatography (HPLC) and the point of care AlereTM Afinion with boronate fixation. We compared first- and second-phase data with respect to glycated hemoglobin, mean interstitial blood glucose, time on and above target for hypoglycemic and hyperglycemic events, and mean hypoglycemic duration. Results: In group A, which received the diabetes education intervention, there was a significant reduction in average HbA1c levels from 8.6% to 7.9% after 3 months (p = 0.001). However, there was no significant difference in average glycemic values. Time above target decreased significantly from 50.62% to 29.43% (p = 0.0001), while time below target decreased from 22.90% to 20.21% (p = 0.002). There was no significant change in the number of hypoglycemic events, but the duration of hypoglycemia decreased significantly from 130.35 min to 121.18 min after 3 months (p = 0.0001). In Group B, there was no significant difference in mean HbA1c levels before (7.07%) and after (7.28%) sensor installation. This group maintained lower HbA1c levels compared to the other group. Average blood glucose levels also remained similar before (148.37 mg/dL) and after (154.65 mg/dL) the intervention. Although the time above the target glucose level increased significantly from 35.94% to 48.17%, the time at target decreased from 50.40% to 37.97%. No significant changes were observed in the time below target, the number of hypoglycemic events, or the duration of hypoglycemia. Conclusions: Our findings indicate that utilizing continuous glucose monitoring technology can enhance glycemic control, particularly in motivated, educated, low-income patients dependent on the SUS. To achieve positive results with FreeStyle Libre, it is imperative to allocate resources for multidisciplinary support.